Near‐Infrared Light‐Responsive Cu‐Doped Cs2AgBiBr6. (18th September 2020) - Ji, Fuxiang; Huang, Yuqing; Wang, Feng; Kobera, Libor; Xie, Fangyan; Klarbring, Johan; Abbrent, Sabina; Brus, Jiri; Yin, Chunyang; Simak, Sergei I.; Abrikosov, Igor A.; Buyanova, Irina A.; et al.
Abstract: Lead‐free halide double perovskites (A2 B I B III X6 ) with attractive optical and electronic features are considered to be a promising candidate to overcome the toxicity and stability issues of lead halide perovskites (APbX3 ). However, their poor absorption profiles limit device performance. Here the absorption band edge of Cs2 AgBiBr6 double perovskite to the near‐infrared range is significantly broadened by developing doped double perovskites, Cs2 (Ag:Cu)BiBr6 . The partial replacement of Ag ions by Cu ions in the crystal lattice is confirmed by the X‐ray photoelectron spectroscopy (XPS) and solid‐state nuclear magnetic resonance (ssNMR) measurements. Cu doping barely affects the bandgap of Cs2 AgBiBr6 ; instead it introduces subbandgap states with strong absorption to the near‐infrared range. More interestingly, the near‐infrared absorption can generate band carriers upon excitation, as indicated by the photoconductivity measurement. This work sheds new light on the absorption modulation of halide double perovskites for future efficient optoelectronic devices. Abstract : The absorption band edge of benchmark double perovskite Cs2 AgBiBr6 is significantly broadened to the near‐infrared range through Cu‐doping. It is demonstrated that the absorption extension is due to subbandgap states induced by Cu‐doping; interestingly, these subbandgap states can generate considerable band carriers upon excitation. The results demonstrate the great potential of Cs2 (Ag:Cu)BiBr6 perovskites for near‐infrared light detection and optoelectronic applications.